A review of CDC's Web-based Injury Statistics Query and Reporting System (WISQARS™): Planning for the future of injury surveillance. (June 2017) - Ballesteros, Michael F.; Webb, Kevin; McClure, Roderick J.
Abstract: Introduction: The Centers for Disease Control and Prevention (CDC) developed the Web-based Injury Statistics Query and Reporting System (WISQARS TM ) to meet the data needs of injury practitioners. In 2015, CDC completed a Portfolio Review of this system to inform its future development. Methods: Evaluation questions addressed utilization, technology and innovation, data sources, and tools and training. Data were collected through environmental scans, a review of peer-reviewed and grey literature, a web search, and stakeholder interviews. Results: Review findings led to specific recommendations for each evaluation question. Response: CDC reviewed each recommendation and initiated several enhancements that will improve the ability of injury prevention practitioners to leverage these data, better make sense of query results, and incorporate findings and key messages into prevention practices.